Inclusive entrepreneurship: A call for a shared theoretical conversation about unconventional entrepreneurs - Bakker, Rene M.; McMullen, Jeffery S. (Journal of business venturing, 2023)
Entrepreneurship has the potential to be an inclusive space comprising many types of conventional as well as unconventional entrepreneurs. In this essay we will argue that when it comes to unconventional entrepreneurs—ranging from refugee entrepreneurs and entrepreneurs with a physical or cognitive disability, to elder entrepreneurs, former convict entrepreneurs, and many others—there are important questions we are not asking because we tend to look at each subgroup in isolation. Our central message is that looking for shared wisdom across various groups of unconventional entrepreneurs may facilitate a shared theoretical conversation that aids the transfer of knowledge, prevents silos and the unnecessary reinventing of the wheel, boosts the field's appeal and critical mass, and facilitates a broader exchange of ideas. To facilitate that conversation, we identify who unconventional entrepreneurs are; identify obstacles to a common theoretical conversation and how these obstacles could be overcome; outline a set of common theoretical themes that apply across various groups of unconventional entrepreneurs; and show how further theorizing unconventional entrepreneurs could challenge the community to reach beyond our existing knowledge horizons to develop pioneering entrepreneurship research. •Despite extant stereotypes, entrepreneurship is an inclusive space comprising many types of unconventional entrepreneurs.•Research has studied specific groups of unconventional entrepreneurs, but tends to confine knowledge to each group.•We call for a shared theoretical conversation regarding unconventional entrepreneurs.•Acknowledging similarities could facilitate the transfer of knowledge and prevent reinvention of the wheel.•We identify four questions for all scholars of unconventional entrepreneurship:•[1] How can unconventional entrepreneurs overcome stigma when appealing to stakeholders?•[2] How can entrepreneurial ecosystems be made more open and inclusive?•[3] How can new offerings transcend from niche markets to main markets? And•[4] How does unconventional become conventional?